Alexander Wilson: Queer Parrhesiast. (1st June 2022) - Maynard, Steven
Drawing on and contextualizing the papers of Alexander Wilson (1953-1993), a Toronto-based writer, activist, and horticulturalist, this article explores the reciprocal relationship between Wilson's intellectual and political work. It focuses on Wilson's involvement with The Body Politic during the late 1970s and early 1980s, and highlights Wilson's role in interviewing Michel Foucault in Toronto in 1982. Encompassing feminism, socialism, and environmentalism as part of a critique of narrow notions of 'gay' identity and aesthetics, Wilson's project, it is suggested, prefigured the emergence of queer politics. At the same time, Wilson enacted a queer parrhesia in keeping with Foucault's Toronto lectures on "speaking the truth about oneself."